The Post-Truth Era: An Exploration of the Online Image of the Elderly Population in China - Zhang Yiya (SHS Web of Conferences)
This study investigates the influence of social media on perceptions of and attitudes towards the elderly in the post-truth era. It addresses challenges faced by older adults in navigating online information, including risks related to misinformation and deception. Emphasizing social media's role in shaping public attitudes, the research underscores how negative stereotypes and stigmatization of the elderly are amplified. By targeting audiences aged 15-60 and those 60 and above, data collection involved filtering social media reports on the elderly and conducting surveys to gauge audience perceptions. Statistical analysis reveals age-related differences in attitudes towards the elderly. Findings highlight the necessity for strategies to enhance elderly online experiences, mitigate risks, and challenge stereotypes through targeted educational initiatives. Efforts to foster a more accurate understanding of older adults aim to combat social isolation and enhance their mental well-being, contributing to a nuanced comprehension of social media's impact on perceptions of the elderly.